2017
DOI: 10.1071/rd14393
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reference genes for quantitative real-time polymerase chain reaction in porcine embryos

Abstract: Abstract. To study gene expression and to determine distinctive characteristics of embryos produced by different methods, normalisation of the gene(s) of interest against reference gene(s) has commonly been employed. Therefore, the present study aimed to assess which reference genes tend to express more stably in single porcine blastocysts produced in vivo (IVO) or by parthenogenetic activation (PA), in vitro fertilisation (IVF) and somatic cell nuclear transfer (SCNT) using different analysis programs, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Although the number of DEGs and fold change values were similar for both developmental stages, vitri ed morulae and blastocysts displayed very different transcriptome pro les, with only 12 (three upregulated and eight downregulated) DEGs in common. This is not surprising, considering that stage-speci c gene expression between morulae and blastocysts is characteristic of the preimplantation embryo development [43].…”
Section: Discussionmentioning
confidence: 95%
“…Although the number of DEGs and fold change values were similar for both developmental stages, vitri ed morulae and blastocysts displayed very different transcriptome pro les, with only 12 (three upregulated and eight downregulated) DEGs in common. This is not surprising, considering that stage-speci c gene expression between morulae and blastocysts is characteristic of the preimplantation embryo development [43].…”
Section: Discussionmentioning
confidence: 95%
“…Our results showed that amongst the genes expressing constant patterns (stability) in the human muscle regardless of sex and physiological conditions, the most stable one is the gene of hypoxanthine phosphoribosyl transferase ( HPRT1 ). The establishment of a tissue-specific reference gene can help discriminate both distinctive characteristics, and genetic-based changes in cell functioning among different physiological conditions 36 , 37 , 38 , 39 ; 40 . Precision in the determination of a gene of reference for comparative analysis of the expression of specific proteins is crucial to enable the assessment of factors that are expressed in low quantities in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the selection of nonvalidated or unstable RGs during normalization of GOI may lead to inconsistent or misleading results [11, 37]. The incorrect selection of RGs drastically affects the results [4, 11, 22, 38]. When the expression of lineage-specific markers in differentiated MSCs toward adipocytes, osteoblasts, and chondrocytes was normalized against the most stable RGs (RPLP0 and EEF1A1 for osteogenesis; TBP and YWHAZ for adipogenesis and chondrogenesis) and the least stable RG (EEF1A1 for adipogenesis; B2M for osteogenesis and chondrogenesis), inconsistent results of the relative expression of lineage-specific markers were significantly ( p < 0.0001) identified.…”
Section: Discussionmentioning
confidence: 99%
“…The primers for each RG were designed by Primer 3 Plus software (considering 60°C annealing temperature) and were analyzed for the formation of hairpins, homodimers, and heterodimers using OligoAnalyzer 3.1 software. In order to check the PCR efficiencies, a standard curve of each primer was made from the cycle threshold (Ct) values by a four-fold serial dilution of cDNA (1:10, 1:100, 1:1,000 and 1:10,000) of E-BM-MSCs following the previous protocols [6, 22]. Standard curve parameters such as slope (M), intercept (B), PCR efficiencies (E = 10 -1/slope -1 × 100), and correlation (R 2 ) were calculated using RotorGene Q Series Software (Qiagen, Hilden, Germany) or Excel (Microsoft, WA, USA).…”
Section: Methodsmentioning
confidence: 99%